The General Meeting of Shareholders Based on Notary Rules and Electronic Evidence (Veteran Law Review, 2023)
The purpose of this study was to analyze an event of the General Meeting of Shareholders (GMS) which was held electronically. The legal status of the minutes of the electronic GMS whether as a legal act, a real act or as a mere fact greatly influences its impact as an authentic deed. This means that a mere fact such as the existence of a piece of land that is flooded, the mental state of a person, cannot be proven by an authentic deed. The results of the legal analysis, the GMS event which was held electronically where the shareholders were not in the same meeting place, but attended based on electronic media, there is still a legal loophole for the shareholders to deny the results of the electronic GMS decision. The research was conducted in a juridical normative manner by reviewing regulations, norms and rules as well as concepts as well as related literature. The conclusion that the electronic GMS event is categorized as a mere fact referring to the Virlijden Rule (made, read and signed by all parties simultaneously at the same time) on the authenticity of the deed, so there is a legal loophole for the meeting participants to deny. The research was conducted using the Virlijden Rule and the Statement of Intention (Wilsverklaring) Rule and also supported by the Deconstruction theory that the interpretation of a text is never single and holds the potential for new and unexpected interpretations. As a legal act from the shareholders for the statement of their will, additional evidence is needed from the shareholders. The meeting participants make separate statements to be submitted electronically to the chairman of the meeting in addition to fingerprints or electronic signatures (e-signature) as regulated in the notary position law.